2006
DOI: 10.1111/j.1365-2133.2006.07484.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of 5-aminolaevulinic acid, methyl 5-aminolaevulinate and hexyl 5-aminolaevulinate on normal human skin

Abstract: The concentrations inducing half of the maximal PpIX fluorescence are around 2% for ALA, 8% for MAL and 1% for HAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 65 publications
(133 reference statements)
5
47
4
Order By: Relevance
“…ALA and MAL produce the same intracellular photosensitizer (PpIX), penetrate human skin to similar depths and produce a similar spatial distribution of PpIX in murine skin . However, ALA produces relatively greater amounts of PpIX (Juzeniene et al, 2006) and higher levels of fluorescence with a slower time course than MAL in human skin (Lesar et al, 2009). This, together with greater local edema reported after ALA compared with MAL-PDT in mice and the possibility of different microscopic PpIX distributions following ALA and MAL application to human skin, could explain the greater immunosuppression observed after ALA-PDT in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…ALA and MAL produce the same intracellular photosensitizer (PpIX), penetrate human skin to similar depths and produce a similar spatial distribution of PpIX in murine skin . However, ALA produces relatively greater amounts of PpIX (Juzeniene et al, 2006) and higher levels of fluorescence with a slower time course than MAL in human skin (Lesar et al, 2009). This, together with greater local edema reported after ALA compared with MAL-PDT in mice and the possibility of different microscopic PpIX distributions following ALA and MAL application to human skin, could explain the greater immunosuppression observed after ALA-PDT in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…Follicles and sebaceous glands are localized relatively deeply in the skin. 38 Christiansen et al 2 suggested that liposome-loaded ALA is preferentially absorbed in hair follicles. The nanoemulsions developed in this work likely exerted similar effects as liposomes.…”
mentioning
confidence: 99%
“…Because factors other than MAL concentration can affect the metabolism of MAL to porphyrins, it is unlikely that local porphyrin accumulation is strictly proportional to local MAL concentration. However it is well established that porphyrin accumulation increases with increasing concentrations of ALA and MAL [26][27][28]. Fluorescence microscopy of porphyrins is a surrogate for indirectly visualizing ALA or MAL uptake in skin.…”
Section: Introductionmentioning
confidence: 99%